Fertility Restoration: Microenvironment‐Protected Exosome‐Hydrogel for Facilitating Endometrial Regeneration, Fertility Restoration, and Live Birth of Offspring (Small 11/2021). Issue 11 (18th March 2021) - Lin, Jiaying; Wang, Zhen; Huang, Jialyu; Tang, Shengluan; Saiding, Qimanguli; Zhu, Qianqian; Cui, Wenguo
Abstract : In article number 2007235, Qianqian Zhu, Wenguo Cui, and co‐workers develop an exosome‐hydrogel through Ag + ‐S dynamic coordination and fusion with adipose stem cell‐derived exosomes, yielding an injectable hydrogel with antibacterial activity that promotes neovascularization and endometrial tissue regeneration. This microenvironment‐protected exosome‐hydrogel system offers a convenient, safe and noninvasive approach for repairing thin endometrium and fertility restoration which is sufficient to restore fertility and improve pregnancy and birth rates.